Non-pustular annular psoriasis with signs of high disease activity - Yasnova, Nevi; Budianti, Windy Keumala; Andardewi, Melody Febriana (Journal of General - Procedural Dermatology and Venereology Indonesia, 2022)
Background: Non-pustular annular psoriasis is a rare condition in which a type of plaque psoriasis appears with ring-like lesions and a clearer central appearance. The disease activities in psoriasis may be evaluated clinically. It is essential to provide a more meaningful approach to treatment management. Case illustration: A 33-year-old woman complained of a one-year history of multiple erythematous, scaly, and annular plaques with central clearing. Some lesions were surrounded by discrete pinpoint papules on several parts of her body. The lesions worsened during seven weeks of topical and systemic therapy. Discussion: Psoriasis is a chronic, multisystem inflammatory disease with predominantly skin and joint involvement. High disease activity or unstable psoriasis was defined as recent exacerbations showing pinpoint papules developing around established and erythematous borders of the lesions. The active severe disease may present with systemic involvement due to the production of pro-inflammatory chemokines and cytokines in the skin lesions and circulation. Conclusion: A complete clinical history and physical examination can help the clinician diagnose non- pustular annular psoriasis. Several factors may cause worsening disease activity in a patient with psoriasis. Distinguishing between stable and unstable plaque psoriasis is essential to obtain information on psoriasis pathomechanism related to systemic involvement and managing therapeutic strategies. A multidisciplinary approach must be conducted in the management of a patient with high disease activity.